The association of family and peer factors with tobacco, alcohol, and marijuana use among Chilean adolescents in neighborhood context - Horner P; Grogan-Kaylor A; Delva J; Bares CB; Andrade F; Castillo M (Dove Medical Press, 2011)
Pilar Horner1, Andy Grogan-Kaylor2, Jorge Delva2, Cristina B Bares3, Fernando Andrade4, Marcela Castillo51School of Social Work, Michigan State University, East Lansing, MI, USA; 2School of Social Work, University of Michigan, Ann Arbor, MI, USA; 3School of Social Work, Virginia Commonwealth University, Richmond, VA, USA; 4School of Education, University of Michigan, Ann Arbor, MI, USA; 5Instituto de Nutrición y Tecnología de los Alimentos (INTA), Universidad de Chile, Santiago, ChileAbstract: Research on adolescent use of substances has long sought to understand the family factors that may be associated with use of different substances such as alcohol, tobacco, and marijuana. However, scant attention has been focused on these questions in Latin American contexts, despite growing concerns about substance use among Latin American youth. Using data from a sample of 866 Chilean youth, we examined the relationship of family and neighborhood factors with youth substance abuse. We found that in a Latin American context, access to substances is an important predictor of use, but that neighborhood effects differ for marijuana use as opposed to cigarettes or alcohol. Age of youth, family and peer relationships, and gender all play significant roles in substance use. The study findings provide additional evidence that the use of substances is complex, whereby individual, family, and community influences must be considered jointly to prevent or reduce substance use among adolescents.Keywords: substance use, adolescence, international, peers